Способ получения корундового и муллитокорундового огнеупорного теплоизоляционного материала - Вакалова Т. В. Татьяна Викторовна; Погребенкова В. В. Валерия Валерьевна; Горбатенко В. В. Виктория Валерьевна; Погребенкова Т. В. Тамара Васильевна
опубл. 10.09.09